Hubungan antara Pola Asuh Orangtua dengan Perkembangan Kognitif Anak Usia Dini - Muslimah Chusnandari; Ichsan Ichsan (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2018)
This study aims to find out: 1) What is the type of parenting in Class B children in ABA Kindergarten Sidoharjo, 2) What is the level of cognitive development in Class B children in ABA Kindergarten Sidoharjo, 3) How is the relationship between parenting and cognitive development in children in kindergarten ABA Sidoharjo especially class B. This type of research is a quantitative quantitative study with a population of class B, ABA Sidoharjo kindergarten, which is 28 children. Data collection uses questionnaires, observation sheets and documentation. Analysis of data using chi square and product moment techniques with the help of SPSS version 18. computer program. The results showed that the type of parenting parents applied to ABA Sidoharjo Kindergarten class B students were 53.6% authoritarian parenting, democratic parenting 39.3% and permissive parenting 7.1%. The level of cognitive development of class B children in ABA Sidoharjo kindergarten includes good cognitive development with a percentage of 14.3%, fairly good cognitive development of 71.4% and unfavorable cognitive development of 14.3%. Then there is a positive relationship between parenting and cognitive development of children, as evidenced by the results of chi square with Asymp. Sig. equal to 0.030 whose probability number is below 0.05. Furthermore, from the three parenting styles that have a positive relationship with cognitive development is the upbringing of democracy as evidenced by the results of r = 0, 744 n p = 0,000. It can be concluded that there is a relationship between parenting parents with cognitive development of children or children with parenting parents, especially parenting democracy will provide good cognitive development, while children with authoritarian parenting will provide adequate or less good cognitive development, so too children with permissive parenting.